2017
DOI: 10.1242/dev.145607
|View full text |Cite
|
Sign up to set email alerts
|

SMC5/6 is required for the formation of segregation-competent bivalent chromosomes during meiosis I in mouse oocytes

Abstract: SMC complexes include three major classes: cohesin, condensin and SMC5/6. However, the localization pattern and genetic requirements for the SMC5/6 complex during mammalian oogenesis have not previously been examined. In mouse oocytes, the SMC5/6 complex is enriched at the pericentromeric heterochromatin, and also localizes along chromosome arms during meiosis. The infertility phenotypes of females with a Zp3-Cre-driven conditional knockout (cKO) of Smc5 demonstrated that maternally expressed SMC5 protein is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 74 publications
0
34
2
Order By: Relevance
“…2D). Specifically, SMC5 for example has been shown to be important for correct segregation of homologous chromosomes during meiosis I in mouse oocytes and, in contrast to our human RNA data, that protein levels of SMC5/6 declined in mice oocytes with age (Hwang et al, 2017). Why did we observe an increase in the RNA-levels of chromosome segregation genes with age?…”
Section: Maturation Stage Is the Main Differentiator Of Oocyte Transccontrasting
confidence: 75%
“…2D). Specifically, SMC5 for example has been shown to be important for correct segregation of homologous chromosomes during meiosis I in mouse oocytes and, in contrast to our human RNA data, that protein levels of SMC5/6 declined in mice oocytes with age (Hwang et al, 2017). Why did we observe an increase in the RNA-levels of chromosome segregation genes with age?…”
Section: Maturation Stage Is the Main Differentiator Of Oocyte Transccontrasting
confidence: 75%
“…Since Nestin is expressed in progenitor cells of tissues other than neural, some degree of DNA excision was also observed in kidneys and muscles in our samples ( Figure 1B and Figure 1-figure supplement 1A) (Bernal et al, 2018;Sakairi et al, 2007). SMC5 depletion in the developing mouse cortex resulted in a significant increase in cleaved caspase 3 (CASP3)-positive cells in Smc5 cKO compared to controls in both, E13.5 and E16.5 cortices ( Figure We have previously shown that the depletion of SMC5 in mESCs causes chromosome segregation defects during mitosis (Hwang et al, 2017;Pryzhkova and Jordan, 2016). Thus, we analyzed VZ and SVZ mitotic progenitors in cortical sections of E13.5 and E16.…”
Section: Smc5 Cko Causes Neurodevelopmental and Sensorimotor Defects mentioning
confidence: 97%
“…Structural maintenance of chromosome 5/6 (SMC5/6) is an evolutionarily conserved protein complex ( 14 , 15 ) that consists of SMC5 and SMC6 along with the NSE1, -2, -3, and -4 proteins ( 16 18 ) and plays irreplaceable roles in DNA repair, chromosome segregation, and telomere length maintenance ( 19 22 ). Interestingly, in addition to its essential role in chromosome maintenance, the SMC5/6 complex was identified as a host restriction factor against HBV ( 23 25 ), but the detailed mechanism underlying the function of the complex in silencing DNA viruses and episomal plasmids remains unknown.…”
Section: Introductionmentioning
confidence: 99%